PEDAGOGICAL ERUDITION IS AN IMPORTANT FACTOR IN TRAINING QUALIFIED PERSONNEL (Universal International Scientific Journal, 2026)
This article analyzes the content of pedagogical erudition, its importance in the educational process and its role in the training of highly qualified personnel. It highlights that in the modern education system, the breadth of knowledge, professional skills and pedagogical erudition of a teacher are important factors in the quality of education and the training of future specialists.
Keywords: pedagogical erudition, pedagogical skills, quality of education, professional competence, highly qualified personnel.